STUDY OF NUCLEAR LEVEL DENSITY AND SPIN CUT-OFF FACTORS (Journal of Sciences, Islamic Republic of Iran)
Nuclear level densities and spin cut-off factors have been deduced for nuclei in the mass region 24‹A‹63,from a microscopic theory, which includes nuclear pairing interaction. Single particle levels for both Seeger and Nilsson potentials were used in the calcdations. Level densities extracted from the theory are compared with their conesponding experimental values, It is found that the overall agreement between experimental level densities and the microscopic theory with pairing is very good. The calculational procedure to account for an odd particle system blocking, as well as the effect of such blocking, is also discussed